Mathematical model of electric field in the zone of insulation peeling off the pipe surface under cathodic polarization - V. V. Lukovich; V. V. Lukovich (Геофизический журнал, 2013)
Mathematical model of potential and current density distributions within delamination area of pipe insulation has been proposed. Results of calculations have been given.